Neuropathic pain induced by spinal cord injury: Role of endothelin ETA and ETB receptors. (23rd March 2016) - Forner, S.; Martini, A.C.; de Andrade, E.L.; Rae, G.A.
Highlights: We evaluated the role of endothelin receptors in neuropathic pain due to traumatic thoracic spinal cord injury in rats. There is a hyperalgesia in rats hindpaws after thoracic spinal cord injury. There is an upregulation of endotelial rececptor ETA on the spinal cord and DRG due to the spinal cord injury. Blocking the ETA receptors with a specific and/or dual-selective antagonist reduces pain. Abstract: Spinal cord injury (SCI) is a devastating neurologic disorder that often inflicts neuropathic pain, which further impacts negatively on the patient's quality of life. Endothelin peptides, which exert their effects via endothelin A (ETA R) and endothelin B (ETB R) receptors, can contribute to sensory changes associated with inflammatory and neuropathic pain, but their role in nociception following SCI is unknown. At different time points after subjecting male Wistar rats to surgery for compression-induced T10 level SCI, the spinal cord levels of ETA R and ETB R were assessed by Western blot and immunohistochemistry, and the corresponding mRNAs by real-time PCR, alongside recordings of behavioural responses to mechanical stimulation of the hind paws with von Frey hairs. SCI was associated with development of hind paw mechanical allodynia from day 14 onwards, and up-regulation of ETA R and ETB R mRNA in the spinal cord and dorsal root ganglia, and of ETA R protein in the spinal cord. SCI increased ETA R protein expression in spinal grey matter. Treatment on day 21 after surgery with the ETA R selective antagonist BQ-123 (40 and 90 pmol, intrathecally) or the dual ETA R/ETB R antagonist bosentan (30 and 100 mg/kg, orally) transiently reduced SCI-induced mechanical allodynia, but the ETB R antagonist BQ-788 was ineffective. Altogether, these data show that SCI upregulates ETA R expression in the spinal cord, which appears to contribute to the hind paw mechanical allodynia associated with this condition. Therapies directed towards blockade of spinal ETA R may hold potential to limit SCI-induced neuropathic pain.